Genetics against race: Science, politics and affirmative action in Brazil. (December 2015) - Kent, Michael; Wade, Peter
This article analyses interrelations between genetic ancestry research, political conflict and social identity. It focuses on the debate on race-based affirmative action policies, which have been implemented in Brazil since the turn of the century. Genetic evidence of high levels of admixture in the Brazilian population has become a key element of arguments that question the validity of the category of race for the development of public policies. In response, members of Brazil's black movement have dismissed the relevance of genetics by arguing, first, that in Brazil race functions as a social – rather than a biological – category, and, second, that racial classification and discrimination in this country are based on appearance, rather than on genotype. This article highlights the importance of power relations and political interests in shaping public engagements with genetic research and their social consequences.